A dimensão de gênero na análise sociológica de desastres: conflitos entre desabrigadas e gestoras de abrigos temporários relacionados às chuvas - Siena, Mariana (2009)
The increase of extreme events related to rains, added to a vulnerable territory insertion of the poorest, generated an increase in the number of homeless across the country. Homeless are those whose home-use buildings suffered damage and / or were destroyed, causing the disintegration of private living space. Among the actions of Civil Defense in a disaster, the priority rehabilitation is the organization of temporary shelters for the homeless families. In a circumstance in which climate change may cause an increase of extreme events related to rainfall, the vulnerability of poor populations tends to grow. It follows then, the need of the improvement of this public service. Considering this, the general goal, is a sociological analysis on the logic by which the measure of Civil Defense has been operating and coordinating the various agencies and the priority actions, such as welfare, health and others. As specific goal, this project aims to focus on the cut of gender, comparatively analyzing the management challenges of shelter, from the perspective of women in position of command and of those who were sheltered. It is considered that the comparative analysis have relevance in the promotion of adjustments in public policies that require integrated activity of various agencies. It is expected that the qualitative research - from a literature, documentary and field review, and from the collect of oral reports, direct observation and photos - provides grants for public management including the theme of emergency with the promotion of citizenship.